Regulated and liberated bodies of schoolgirls in a Finnish short film from the 1950s - Nieminen Marjo (Routledge, 2022)
This article focuses on the bodies of schoolgirls as visualised and represented in a short film of Finnish secondary schools for girls in the 1950s. The film, Oma tyttökouluni (My own girls’ school) was released in 1957 and was screened in cinemas in advance of feature films. Although the short film was made in a documentary style, it also includes the undertone of a fictionalized narrative. This article explores the representations of schoolgirls’ bodies in the visual narrative of the film and examines how the imagery is interwoven with the social contexts and atmosphere of the 1950s and the tradition of Finnish short film production. The paper discusses how the filmic elements create an almost romanticised image of the everyday life in schools and the visualised bodies of the schoolgirls. It examines how the representations of female bodies and girlhood in the school context in the short film construct the imagery of guidance for middle class values, acceptable appearances and manners. In addition, the film depicts the sites of freedom where the female bodies were liberated from the choreography of schooling and the normative rules and routines of the school. The paper argues that the harmonious nature of the film lacks contradictions and contains the ideological connotations and middle class values of the Finnish post-war secondary schooling that girls received.